VECTOR VALUED FIELDS - Trenčevski, Kostadin (Matematichki Bilten, 1994)
In this paper we introduce \((n,m)\)-fields and fully commutative \((n,m)\)-fields, as a continuation of the vector valued groups and fully commutative vector valued groups. Further we give some examples of the introduced structures.